ANALISIS SISTEM INFORMASI MANAJEMEN PADA RUMAH SAKIT BETHESDA YOGYAKARTA DENGAN STANDAR COBIT 2019 - Raditya Rahardyansyah Rifat (2023)
Hospitals are health service institutions that must meet standards to maintain service quality. Bethesda Hospital, for example, has the motto "Please First Back Affairs" and is required to provide fast, efficient, effective, and safe services. To achieve this, an information system is needed that can help daily operations in the hospital. Information System Management is very important in healthcare, because easily accessible information affects service time and patient satisfaction. The flow of information in health management affects service operations and patient trust in hospitals. Therefore, information system management needs to be done to maintain and improve the quality of hospital services. Review results from the RS mobile application. Bethesda Yogyakarta showed complaints regarding registration, medical record numbers, and inappropriate schedules. Therefore, management analysis of hospital information systems with recognized and accountable standards is needed. The standard used is COBIT 2019, which is a framework for corporate information and technology governance and management. COBIT 2019 is divided into 5 domains with two different objective domains, which is the reason for its use in hospital information system management analysis. This research uses interview methods, literature studies, direct observation, questionnaires using Likert scales as well as through relevant important documents. The data processing method using SPSS software is followed by validity and reliability tests. The results of this study are in the form of the results of the maturity level analysis of the management information system at Bethesda Hospital Yogyakarta which is based on aspects of the domains used in this study, namely the EDM03, APO12, APO13, BAI10, and DSS04 domains.